APLIKASI LOGIKA FUZZY UNTUK MENENTUKAN UANG KULIAH TUNGGAL (UKT) - Siti Maslihah (Jurnal Riset Pembelajaran Matematika, 2019)
This research is motivated by the regulation of Government Regulation No. 55 of 2013 concerning the Single Tuition Policy (UKT) at the State Higher Education Institution. The UKT is related to the education costs that must be paid by students according to the economic conditions of students. The implementation of this regulation still faces several obstacles, including the appeal of UKTs that occur every year since the enactment of this rule. This appeal was driven by a sense of dissatisfaction from parents of students towards the UKT group that was imposed on their sons / daughters. Departing from the problem, the researcher wants to apply an application to assist in determining the student UKT class based on fuzzy logic (fuzzy logic). The methods used in this study are literature studies, documentation and interviews with related parties. Literature studies are used to create a UKT group determination program, documentation is used to record data that has been uploaded by students during registration, and interview methods to extract information needed from data sources. The results of this study are a program that utilizes the Fuzzy Inference System in the MATLAB toolbox. The program trial was conducted on 96 students and the results showed that there were differences in the acceptance of UKT funds when using non-fuzzy programs and with fuzzy programs. The results obtained are there are differences in university acceptance of 0.203% greater by using fuzzy programs. From this study it can be concluded that fuzzy logic can be used to determine the student UKT group with the help of fuzzy inference system in the MATLAB toolbox.